How Well Does Renal Transplantation Cure Hyperparathyroidism?. Issue 4 (October 2015) - Lou, Irene; Foley, David; Odorico, Scott K.; Leverson, Glen; Schneider, David F.; Sippel, Rebecca; Chen, Herbert
Abstract : Background: Most patients with end-stage renal disease will develop hyperparathyroidism (HPT). Transplantation reportedly resolves HPT in most cases. Currently, guidelines recommend a watchful waiting approach to HPT for the first 12 months after the transplantation to allow maximal allograft function. The purpose of our study is to examine the incidence and impact of HPT, defined as an elevated parathyroid hormone (PTH) level, after renal transplantation in a contemporary cohort. Methods: Primary kidney transplantation was performed on 1609 patients from January 1, 2004, to June 6, 2012. Patients were stratified by timing of achieving normal serum PTH levels, and a multivariate logistic regression was constructed to determine predictive variables. Kaplan–Meier analysis was then performed on overall graft survival based on PTH normalization. Results: Four hundred eighty-eight (30.3%) patients achieved normal PTH within 1 year posttransplant. Four hundred twenty-seven (26.6%) attained normal PTH between 1 and 2 years, with the remaining 694 (43.1%) categorized as having HPT. Patients achieving normal PTH within 12 months of transplantation had a significantly longer median graft survival (7.33 years) compared with those patients who normalized between 12 and 24 months (4.92 years, P < 0.001), and those with HPT (5.13 years, P < 0.001). Comparing normalization of PTH by 2 years to HPT patients, obesity ( P < 0.001), months on dialysis ( P < 0.001), and delayed graft failure ( P = 0.006) were predictive of nonnormalization. Overall, allograft survival analysis revealed a survival advantage for patients who normalize PTH within 24 months of transplantation ( P = 0.038). Conclusions: Renal transplant resolves HPT in 56.9% of patients at 2 years. Resolution within the first year portends longer graft survival. Therefore, earlier intervention for HPT should be considered.